Knowledge Management through Groupware Technology - Alcoforado, Elidomar (2019)
This work aims to analyse how the use of groupware technology influences the process of knowledge management, in the largest Brazilian electricity company. The study, based on a qualitative approach, analysis different groupware technology tools and their relationship as facilitators of knowledge management. The results suggest that groupware technology deployed in the company has facilitated the operational work and improved the informational level in the company, from information management, but is not used systematically for the transfer and sharing of organisational knowledge.